Investigation of absorption kinetics by the phase plane method - Dokoumetzidis, A.; Macheras, P. (PHARMACEUTICAL RESEARCH, 1998)
Purpose. To develop a simple approach for investigating absorption kinetics, which does not require modeling assumptions or intravenous data. Methods. The concentration (C) -time (t) data are plotted as a phase plane plot (dC/dt versus C). Errorless C,t data were generated from one and two compartment models employing first-order, zero-order and Michaelis-Menten input kinetics, and the phase plane plots were constructed. A simple test based on the ratio of slopes of the separate linear regression analyses of absorption and elimination data of the phase plane plot is proposed to justify or not the presence of zero-order input kinetics. Errant data were used to assess the performance of the test developed. Literature data of theophylline and nitroglycerin formulations were analyzed using the phase plane plot. Input rate-time profiles were constructed for one compartment model drugs utilizing the data of the phase plane plot. Results. The geometric forms of the phase plane plots derived from the errorless data of the various pharmacokinetic models were found to be indicative of the absorption kinetics. Very good results were obtained when the test for the discernment of absorption kinetics was applied to errant data. Zero-order absorption kinetics were justified (i) for the transdermal absorption of nitroglycerin and (ii) only for a certain period of time, for the gastrointestinal absorption of theophylline. Conclusions. Investigation of absorption kinetics can be accomplished with the phase plane method. The cumulative character of the classical percent absorbed versus time plots can be misleading in justifying the presence of zero-order input kinetics.
Keywords: Absorption; absorption kinetics; phase plane; phase plane method; zero-order